Economic growth in an oil-dominant economy of Nigeria: The role of financial system development - Oliver E. Ogbonna; Ikechukwu A. Mobosi; Okwudili W. Ugwuoke (Cogent Economics & Finance, 2020)
This paper examines the effect of financial system development on oil-dominant economy of Nigeria using Zivot-Andrews unit root test and Autoregressive Distributed Lag (ARDL) model over the period 1981 to 2015. The motivation of this paper is that the study distinguished the impact of financial system development on the non-oil sector from the oil sector. The study also differs from the usual yet unsatisfactory approach of measuring financial system development in Nigeria to build an index as a measure that characterizes the whole development in the financial sector using Principal Components Analysis (PCA). The result reveals that there exist mediating factors that alter the impact of finance on growth. Specifically, the findings indicate that financial system development has a negative and insignificant impact on the growth of oil sector while the influence of financial system development on the growth of non-oil sector is positive and significant. The study therefore recommend that policymakers should channel the high receipts from the export of crude to productive investments through financial institutions that will allocate the resources more efficiently to improve the quality of investment capable of driving growth.
Keywords: E51; G21; O47; Q41; 330; ARDL method; economic growth; financial system development; non-oil sector; oil sector